1974
DOI: 10.1126/science.184.4138.800
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Regulation of Chlorophyll Synthesis Analyzed with Mutants in Barley

Abstract: Barley seedlings homozygous both for the xantha-1(35) and tigrina-d(12) mutation accumulate magnesium protopophyrins and other precursors of chlorophyllide constitutively in darkness. The homozygous double mutant xantha-f(10), tigrina-O(34) produces protoporphyrin constitutively. These results provide evidence for the control of chlorophyllide synthesis in higher plants through the products of regulatory genes in the nucleus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
62
0

Year Published

1974
1974
2006
2006

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(62 citation statements)
references
References 6 publications
0
62
0
Order By: Relevance
“…(c) We have recently identified a regulatory mutant which enhances PROTO accumulation of both brc-I and br,-I about 30-fold, while having a wild-type phenotype by itself (Wang, Boynton, GiUham, and Gough, in preparation). This mutant may be similar to the tig-d regulatory mutant in barley described by von Wettstein et al (1974). In spite of the well recognized fact that magnesium is inserted into the PROTO molecule to form Mg-PROTO, the manner in which this reaction proceeds in vivo is still unknown (Burnham, 1969).…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…(c) We have recently identified a regulatory mutant which enhances PROTO accumulation of both brc-I and br,-I about 30-fold, while having a wild-type phenotype by itself (Wang, Boynton, GiUham, and Gough, in preparation). This mutant may be similar to the tig-d regulatory mutant in barley described by von Wettstein et al (1974). In spite of the well recognized fact that magnesium is inserted into the PROTO molecule to form Mg-PROTO, the manner in which this reaction proceeds in vivo is still unknown (Burnham, 1969).…”
Section: Discussionmentioning
confidence: 58%
“…Barley mutants blocked at various steps in the pathway prior to PCHLD do not accumulate detectable amounts of porphyrin intermediates in darkness. Such porphyrins are accumulated only when these mutants are fed ALA (Gough, 1972) or are combined with regulatory mutants (von Wettstein et al, 1974). Thus in higher plants several of the intermediates in the chlorophyll biosynthetic pathway including PRO-TO are thought to exert a regulatory effect on the synthesis of ALA (Gough, 1972, von Wettstein et al, 1974.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A prerequisite for further studies of the genetic regulation of chlorophyll biosynthesis (9,13,21) is the isolation and characterization of the enzyme(s) converting glutamate into baminolevulinate (ALA) (3,4). Recently it has been shown that ALA formation can be carried out by isolated intact immature chloroplasts of spinach (7) and cucumber (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…In plants ALA is the limiting metabolite for chlorophyll formation and the enzyme system forming ALA is strictly regulated. It has been proposed that this regulation operates at the level of repression and/or feedback inhibition (4,7,18,19). As a first step for obtaining precise information about the nature of the genetic control of chlorophyll synthesis we GOUGH • KANNANGARA : (~ .aminolevulinate synthesis have isolated a cell-free preparation from developing leaves which catalyses the formation of ALA.…”
Section: Introductionmentioning
confidence: 99%